Circular RNA hsa_circ_0000848 Promotes Trophoblast Cell Migration and Invasion and Inhibits Cell Apoptosis by Sponging hsa-miR-6768-5p - Wang, Hui; Zhang, Jianming; Xu, Zhiyong; Yang, Jingxin; Xu, Yong; Liu, Yang; Li, Bohong; Xie, Jiansheng; Li, Jing (Frontiers in Cell and Developmental Biology, 2020)
Background: Fetal growth restriction (FGR) is a worldwide problem, and the second most common cause of perinatal death. The precise molecular mechanisms involved in placental development and function during FGR remain poorly understood. Circular RNAs (circRNAs) are important biological molecules associated with disease pathogenesis. However, the role of circRNAs in FGR has not been well studied. Methods: circRNA expression profiles in placental tissues with and without FGR were identified by circRNA microarray. circRNA expression was verified by quantitative reverse-transcription PCR (RT-qPCR) assay. The effect of hsa_circ_0000848 and has-miR-6768-5p on HTR-8 cell apoptosis, migration, and invasion was evaluated. The association between hsa_circ_0000848 and hsa-miR-6768-5p was confirmed by dual luciferase activity and anti-AGO2 RNA immunoprecipitation (RIP) assays. Protein levels were examined via western blotting. Results: Microarray analysis results showed that a total of 13532 circRNAs were identified in placental tissues with and without FGR. Of these, 100 and 144 circRNAs were more up- and down-regulated, respectively, in the FGR group compared to the normal placental tissues. Moreover, RT-qPCR results showed that hsa_circ_0000848 expression was significantly down-regulated in FGR placenta. Hsa_circ_0000848 overexpression and has-miR-6768-5p inhibitor suppressed apoptosis, and promoted cell migration and invasion. In addition, hsa_circ_0000848 overexpression and has-miR-6768-5p inhibitor increased the protein abundance of BCL2, MMP2 and MMP9 and decreased the protein abundance of cleaved caspase-3, cleaved caspase-9, and BAX, whereas hsa_circ_0000848 knockdown caused the opposite effect. Moreover, a significant increase in hsa-miR-6768-5p expression and a negative correlation between hsa_circ_0000848 and miR-6768-5p were identified in the FGR tissues. Luciferase reporter and RIP assay results revealed binding of miR-6768-5p to hsa_circ_0000848. Furthermore, hsa-miR-6768-5p overexpression eliminated the effect of hsa_circ_0000848 overexpression in HTR-8 cells. Conclusions: hsa_circ_0000848 expression is significantly down-regulated in the FGR placenta. hsa_circ_0000848 promotes trophoblast cell migration and invasion, and inhibits cell apoptosis via the sponging of hsa-miR-6768-5p. Our study provided a novel insight into mechanisms underlying the pathogenesis of FGR, as well as into new strategies for the treatment of FGR.